Synthesis, characterization, and biological screening of metal nanoparticles loaded gum acacia microgels - Ihsan, Junaid; Farooq, Muhammad; Khan, Muhammad Aslam; Ghani, Marvi; Shah, Luqman Ali; Saeed, Shaukat; Siddiq, Mohammad (Microscopy research and technique, 2021)
We report novel gum acacia (GA) based microgels composites for multifunctional biomedical application. High yield of spherical GA microgels particles within 5–50 μm size range was obtained via crosslinking the polymer in the reverse micelles of surfactant‐sodium bis (2‐ethylhexyl) sulfosuccinate (NBSS) in gasoline medium. The prepared microgels were then utilized for in situ silver (Ag) and cobalt (Co) nanoparticles (NPs) synthesis to subsequently produce GNAg and GNCo nanocomposite microgels, respectively. Ag and Co NPs of particle of almost less than 40 nm sizes were homogenously distributed over the matrices of the prepared microgels, and therefore, negligible agglomeration effect was observed. Pristine GA microgels, and the nanocomposite microgels were thoroughly characterized through FTIR, DSC, TGA, XRD, SEM, EDS, and TEM. The well‐characterized pristine GA microgels and the nanocomposite microgels were then subjected to multiple in vitro bioassays including antioxidant, antidiabetic, and antimicrobial activities as well as biocompatibility investigation. Our results demonstrate that the prepared nanocomposites in particular GNAg microgels exhibited excellent biomedical properties as compared to pristine GA microgels. Among the prepared samples, GNAg nanocomposites were highly active against Fusarium oxysporum and Aspergillus niger that show 47.73% ± 0.25 inhibition and 32.3% ± 2.0 with IC‐50 of 220 μg ml−1 and 343 μg ml−1, respectively. Moderate antidiabetic activity was also observed for GNAg nanocomposites with considerable inhibition of 15.34% ± 0.20 and 14.7% ± 0.44 for both α‐glucosidase and α‐amylase, respectively. Moreover, excellent antioxidant properties were found for both the GNAg and GNCo nanocomposites as compared to pristine GA microgels. A remarkable biocompatible nature of the nanocomposites in particular GNAg makes the novel GA composites, to be exploited for diverse biomedical applications. Gum acacia hydrogels were synthesized via water‐in‐oil micro‐emulsion polymerization technique Gum acacia hydrogels were used as template for in situ metal NPs preparation Gum acacia‐metal nanocomposites hydrogels were highly biocompatible as well as excellent fungicidal, anti‐oxidant, and anti‐diabetic in nature.